Extraction of magnetite from millscales waste for ultrafast removal of cadmium ions - Ahmad Nazri, Nur Asyikin; Azis, Raba’ah Syahidah; Che Man, Hasfalina; Ismail, Ismayadi; Ibrahim, Idza Riati (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This research was conducted to produce the magnetite (Fe3O4 ) nanoparticles extracted from the industrial millscale waste. Then, the micron size samples were extracted and grounded on the high energy ball milling (HEBM) at various milling time for 4, 8, 12, 16 and 20 h. The formation of nanosized single-phase hexagonal spinel has been observed with XRD analysis as early as 4 h milling time. The FTIR transmission spectrum shows the appearance of a Fe-O functional group for each sample. HRTEM images showed that all the samples had a small particle size of 5-20 nm with uniform distribution. The specific surface area of the 5 adsorbents increased after the 8 h milling time and it showed reduction after that. The magnetite adsorbents then utilized the adsorbent in Cadmium ions removal of the aqueous solution. Fe3O4 with 8 h milling time was able to remove 9.81 mg of cadmium ions with 1 g of adsorbents consume. The removal of the cadmium ions detected related to the particles size, surface areas and saturation magnetization. This research successfully revealed that the higher saturation magnetization contributed to high removal percentages in cadmium ions of aqueous solutions. Fe3O4 extraction from mill scales waste is cost-effective, the process is eco-friendly and thus, potentially to be applied for wastewater treatment.